Re-Design Application Mobile “Wallet” With Method Lean UX - Efendi, Yoyon; Gunadi; Muzawi, Rometdo; Utami, Nurul (STMIK Amik Riau, 2023)
Wallet is a financial product service designed to simplify the payment process. Through Wallet, users can make transactions independently without having to go to a bank branch or ATM. Apart from that, the existence of Wallet helps reduce customer queues at ATMs. To increase the number of transactions via Wallet and make service quality effective and efficient, improvements to Wallet features and design are needed. It is still incomplete and no longer attractive, so Wallet usage has decreased. Therefore, User Interface (UI) and User Experience (UX) design is needed as a basis for building a platform to create more attractive designs and features. The Lean UX method focuses on user satisfaction with the user interface created, so this method was chosen in this research to develop the user interface design. Based on analysis, implementation and evaluation, the final prototype is a combination of prototypes A and B which have been validated in terms of appearance, as well as criticism and suggestions from consumer users and technicians. Prototype A was selected for 5 features and Prototype B was selected for 5 features. On the logo page select design A with a percentage of 72.2%, on the main menu page select design A with a percentage of 80.6%, on the home page select design A with a percentage of 69.4%, on the account information page select design A with a percentage of 75%, and the selected transfer page was design B with a percentage of 55.6%. In addition, this research produces results that have a consistent user interface in terms of colors, fonts, images and layout as well as a user experience that makes it easy for users to understand the information to use the application and get it as needed.